Measuring Nursing Care Time and Tasks in Long-Term Services and Supports: One Size Does Not Fit All - Bettger, Janet Prvu (J Nurs Res, 2012)
BACKGROUND: Although nursing care personnel comprise the majority of staff in long-term care services and supports (LTSS), a method for measuring the provision of nursing care has not yet been developed. PURPOSE/METHODS: We sought to understand the challenges of measuring nursing care across different types of LTSS using a qualitative approach that included the triangulation of data from three unique sources. RESULTS: Six primary challenges to measuring nursing care across LTSS emerged: level of detail about time of day, amount of time, or type of tasks varied by type of nursing and organization; time and tasks were documented in clinical records and administrative databases; data existed both on paper and electronically; several sources of information were needed to create the fullest picture of nursing care; data was inconsistently available for contracted providers; documentation of informal caregiving was unavailable. Differences were observed for assisted living facilities and home and community based services compared to nursing homes and across organizations within a setting. A commonality across settings and organizations was the availability of an electronically stored care plan specifying individual needs but not necessarily how these would be met. CONCLUSIONS: The findings demonstrate the variability of data availability and specificity across three distinct LTSS settings. This study is an initial step toward establishing a process for measuring the provision of nursing care across LTSS to be able to explore the range of nursing care needs of LTSS recipients and how these needs are fulfilled.